2019
DOI: 10.1002/cbdv.201800546
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of the Green Waste from Two Varieties of Fennel and Carrot Cultivated in Tunisia by Identification of the Phytochemical Profile and Evaluation of the Antimicrobial Activities of Their Essentials Oils

Abstract: The purpose of this study was to identify the chemical composition and the antibacterial activity of the essential oils (EOs) extracted from the green tops of Daucus carota L. subsp. sativus (Hoffm.) Arcang. plants producing yellow roots (DcsYR) and those producing orange roots (DcsOR) and from two varieties of Foeniculum vulgare subsp. vulgare cultivated in Tunisia. Analyses revealed that the EOs from the two D. carota varieties were rich in constituents belonging to sesquiterpenes. Phenylpropanoids and non‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Similarly, Ashraf et al studied the effect of Nigella sativa (Black seed) oil against antibiotic-resistant isolates by a well diffusion and microbroth dilution method, and they concluded that N. sativa had in vitro activity against Salmonella Enterica [27]. Chiboub et al evaluated the biological activity of the EOs of two varieties of Foeniculum vulgare in the growth of Salmonella Enterica, and the results showed a significant antimicrobial activity [32]. Aghraz et al showed that EOs from Cladanthus arabicus and Bubonium imbricatum contain a potent activity against the tested Salmonella strain , with MIC values between 200 and 800 μg/mL for C. arabicus and from 400 to 1600 μg/mL for B. imbricatum [25].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ashraf et al studied the effect of Nigella sativa (Black seed) oil against antibiotic-resistant isolates by a well diffusion and microbroth dilution method, and they concluded that N. sativa had in vitro activity against Salmonella Enterica [27]. Chiboub et al evaluated the biological activity of the EOs of two varieties of Foeniculum vulgare in the growth of Salmonella Enterica, and the results showed a significant antimicrobial activity [32]. Aghraz et al showed that EOs from Cladanthus arabicus and Bubonium imbricatum contain a potent activity against the tested Salmonella strain , with MIC values between 200 and 800 μg/mL for C. arabicus and from 400 to 1600 μg/mL for B. imbricatum [25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts made in the last decade to find an alternative use for food waste and by-products, fennel waste remains unused as a raw material to produce high value-added products. The most studied compounds of fennel waste are extracted from the volatile fraction, whereas the polyphenolic compounds have been barely evaluated to date [12]. Recently, Di Donato et al [8] investigated the polyphenolic profile of fennel waste through reverse-phase high-performance liquid chromatography (RP-HPLC) and LC-mass spectrometry (MS) technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded results showed that the Daucus carota subsp. sativus yellow roots oil was significantly more effective against Gram-negative than Gram-positive bacteria, and the MIC values were in the range 6.25-50 mg/mL [56].…”
Section: Agro-food Wastes As Antimicrobialsmentioning
confidence: 95%